Compressive strength of lightweight foamed concrete with charcoal as a sand replacement - Lee, Yeong Huei; Lim, Ming Han; Lee, Yee Ling; Lee, Yee Yong; Tan, Cher Siang; Mohammad, Shahrin; Ma, Chau Khun (National Institute of Science Communication and Information Resources, 2018)
Foamed concrete, a high performance concrete with lightweight properties and strength-enhancing additive have drawn the attention of researchers towards a sustainable life style. This paper presents a study of the compressive strength of various charcoal-filled lightweight foamed concrete (LFC), where waste materials, water-reducing agent and strength enhancement additives are introduced to the mix design in order to obtain further lightweight concrete. Five series of experimental tests were carried out, where Series 1 tested optimum ratio of silica fume and superplasticizer, Series 2 depicted the design mix of sand replacement with charcoal, Series 3 described the mix for additives, Series 4 illustrated effect of aggregate size for charcoal and different densities, as well as Series 5 was the conventional design mix ratio. The fresh and harden densities have been recorded while the shrinkage of LFC had also been observed during the casting and curing period. From the results, the mixture with silica fume replacing the cement was found to have a lower compressive strength as compared to mixtures with a full portion of cement. The strength reductions ranged between 62 to 80% for the mix with no superplasticizer and 29 to 82% for the mix with superplasticizer, which was obtained from the 20 to 50% of cement replacement with silica fume. Foamed concrete with superplasticizer achieved 66% of higher compressive strength. However, concrete expansion and spalling were discovered at the later concrete age of Series 5 which degraded the concrete strength. From this study, it was found that charcoal with low specific gravity is a suitable for full sand replacement in foamed concrete prior to the treatment that can lower its alkalinity.